Smart aquarium / Hairul Anuar Aziz - Aziz, Hairul Anuar (2006)
This thesis presents the implementation of the Smart Aquarium that has the ability to sense and control the dregs of the water and automatic feeding. The system developed is an automatic system and design based on the Peripheral Interface Controller (PIC) that acts as a controller. Certainly, this project consist of software and hardware development where knowledge in PIC programming, electronic and electrical devices are important to make the system operate. Controlling the dregs of the water is done by using dregs sensor connected to the aquarium and controlled by the PIC microcontroller. The Smart Aquarium also has the ability to change the water automatically when the dregs level in the aquarium is detected high. The amount of water in the aquarium is controlled by water level sensor, which placed in the aquarium. The water that added into the aquarium comes from a prefill reservoir located above the aquarium setup. The water is controlled by a solenoid valve which is turned on and off by the PIC microcontroller. The water that drained out of the tank goes into a drain reservoir, which is located below the aquarium setup. A water pump attached to the hose leading to the drain reservoir to generate the suction needed to extract the water from the tank. A servomotor controls the hole of automatic feeder either open or closed. The hole in the cylinder is designed such that only a specified amount of food is released per revolution. The feeding time is set by the user and controlled by the PIC microcontroller.